2016
DOI: 10.1007/s12665-016-5563-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying future changes in glacier melt and river runoff in the headwaters of the Urumqi River, China

Abstract: Climate change is likely to have significant effects on the water cycle in glacierized basins. Here, the glacier-enhanced Soil and Water Assessment Tool (SWAT) was employed to simulate glacio-hydrological processes and to estimate the potential hydrological changes driven by downscaled future climate projections of five Global Circulation Models (GCMs) under three Representative Concentration Pathways (RCPs) in the headwaters of the Urumqi River, Tianshan Mountains, China. The evaluation indices indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The PBIAS values from verification using the modified model were better than that of the model before (Tables 4 and 5). The temperatures in Issyk-Kul's northern and southern catchments begin to rise in early April, snow begins to melt into stream flow, and the water levels in the catchments begin to rise rapidly [25], eventually leading to floods [97][98][99]. Our results showed that the participation of snowmelt from October to March was limited to the modified degree-day method, which increased from April to September.…”
Section: Model Performancementioning
confidence: 79%
“…The PBIAS values from verification using the modified model were better than that of the model before (Tables 4 and 5). The temperatures in Issyk-Kul's northern and southern catchments begin to rise in early April, snow begins to melt into stream flow, and the water levels in the catchments begin to rise rapidly [25], eventually leading to floods [97][98][99]. Our results showed that the participation of snowmelt from October to March was limited to the modified degree-day method, which increased from April to September.…”
Section: Model Performancementioning
confidence: 79%
“…In the Tizinafu River Basin, temperatures usually begin to increase at the end of the March, and snow at the lower elevations starts to melt into the streamflow [8]. This leads to a rapid increase in the water level of the river, an increase in water flow, and a tendency for snow-melting floods [37,[91][92][93]. The contribution of snowmelt to runoff during the non-snow-melting season was limited in the modified degree-day method, which increased peak flooding during the snow-melting season and brought it closer to the measured discharge values.…”
Section: Model Performancementioning
confidence: 99%
“…In previous studies, the analysis of historical climate change trends has mainly based on historical long‐term observational data covering the entire scale of Xinjiang (Jiang and Hu, ; Wu et al ., ; Campbell et al ., ). For the future climate change projections, most studies have mainly focused on watershed scales, including Bosten Lake (Chen et al ., ; Qiu et al ., ) as well as in the Urumqi (Zhang et al ., ), Kaidu (Liu et al ., ; Fang et al ., ), Tarim (Xu et al ., ; Xu et al ., ; Liu et al ., ), and Hotan (Luo et al ., ) river basins. Fewer studies have paid attention to the future patterns of climate change across the entire region as well as the possible circulation mechanisms response for the local climate change.…”
Section: Introductionmentioning
confidence: 99%